Structural shift and increasing variety in Korea, 1960-2010: Empirical evidence of the economic development model by the creation of new sectors - Jung-In Yeon; Andreas Pyka; Tai-Yoo Kim (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
In this paper, we examine the experiences of the Korean economy alongside theoretical knowledge of economic development and structural change. To demonstrate the generalized hypotheses on structural change, input-output tables of Korea, from 1960 to 2010, were analyzed. Our interest in taking time series of input-output tables originates from the following two issues. Firstly, we raise the question of whether Korean industrial structure changes have followed a certain pattern of structural shifts as well as increasing variety. Secondly, if so, it is questioned how the meso-level conditions for economic development could be explained from such a pattern. To search for answers, we adopt a model of the economic development by the creation of new sectors, named TEVECON, as our theoretical framework. Using this growth model, we derive hypotheses about how the structural change could affect economic development, and then we determine how the empirical analysis of the Korean economy verifies and deepens our understanding of structural change and economic development. This paper contributes to the empirical validation of the theoretical knowledge of economic development by the emergence of key sectors and the creation of new industries.
urn:nbn:de:bsz:100-opus-12764
Keywords: D31; D62; O10; O30; 330; Structural change; Increasing variety; Unrelated variety; Input-output table; Korean economy; TEVECON model; Economic development; Economic growth